Educational sustainability: A multi-scale elementary school resource distribution variability from China - Jiali Cai; Wenhua Wei (Heliyon)
The allocation of educational resources is a critical factor in the sustainable development of education. This study developed a framework for assessing educational resource allocation indicators integrating multi-scale and multi-dimensional indicators. China's geographic regions and development periods were analyzed for intra-regional variability, inter-regional variability across different periods, and spatio-temporal coupling variability characteristics. The study reveals that the internal variability of primary education resources in the eastern, central, and western regions of China has significantly decreased, with the Gini coefficient in the western region dropping from 0.40 in 2006 to 0.12 in 2020. The country's macro-policy regulation has steadily reduced the variation in physical educational resources between regions. The spatiotemporally coupled variability indicators demonstrate that the Rural Revitalization Strategy has substantially enhanced educational and physical resources in rural areas. However, the regional variability in the indicator of teachers per capita with graduate degrees continues to widen. The coupling-cumulative variance ratio (CVR) between the eastern urban and western rural areas increased to 1836.53 %, and the western urban and western rural difference ratio increased to 1117.58 %. Based on these findings, the study discusses the characteristics of each sector, utilizing methods of supervision, cooperation, communication, and guidance to create a dynamic mechanism for maintaining equity in educational resources. This study aims to provide methodological and data recommendations for analyzing equitable resource distribution in educational settings across other developing nations and regions.